EVALUASI PROGRAM PENDIDIKAN KARAKTER BERBASIS KETARUNAAN TINGKAT SEKOLAH MENENGAH KEJURUAN DI KABUPATEN BOGOR - Bung Hadi, Abdul; Jahan (Jurnal Gici Jurnal Keuangan dan Bisnis, 2025)
This study aims to evaluate the character education program based on cadetship at SMK Bina Sena Bogor using the CIPP (Context, Input, Process, Product) evaluation model. A mixed methods design was employed, combining quantitative data from questionnaires with qualitative data from interviews, observations, and document analysis. The analysis was conducted integratively to assess the program’s contextual relevance, input feasibility, process dynamics, and product outcomes. The findings reveal that in terms of context, the program aligns with the school’s vision and the maritime industry’s needs, although adjustments are required for today’s learners. Regarding input, regulations and facilities support the program, but instructors’ competencies need further development. In the process aspect, activities run as planned but remain dominated by instructive approaches that may foster bullying. For product, the program improves student discipline, yet responsibility and resilience are not optimally developed. The study concludes that the cadetship program is relevant and urgent, but improvements are needed in more humanistic coaching strategies, instructor capacity-building, and measurable evaluation tools for character development. The findings are expected to provide practical contributions for schools and academic contributions to the development of cadetship-based character education models at the vocational school level